From cultural exchange to identity formation: Intercultural experiences of Indonesian pre-service English teachers in the Philippines - Indawan Syahri; Rini Susanti; Nadya Rezkhita Dwiana (Universitas Muhammadiyah Malang, 2025)
In today's global educational landscape, pre-service teachers must be equipped to teach in culturally diverse classrooms. This research examines three Indonesian pre-service English teachers undertaking teaching practicum in the Philippines as part of the South East Asia-Teacher (SEA-Teacher) program. The objective is to understand their intercultural learning experiences during the practicum and their impact on their identities as educators. This study employs a narrative inquiry methodology, with data collected through in-depth interviews, journal writing, and focus group discussions. The theoretical framework is derived from Byram's (1997) concepts of intercultural communicative competence, Mezirow's (2000) theory of transformative learning, and Norton's (2013) perspectives on identity. The results indicate several key factors that shape the participants’ experiences, including exposure to new educational methods, engagement with diverse cultural norms, and encounters with unfamiliar religious practices. Valuable experiences include acquiring new educational methodologies and embracing diverse cultures. Challenges sometimes arise, such as confusion around religious practices and novel educational methodologies. This significantly influences their self-perception as educators and their confidence in teaching in multicultural classrooms. This research proposes that teacher programs incorporate more foreign practicums to better prepare students for global teaching opportunities